1990
DOI: 10.1123/jtpe.10.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of Preservice Physical Education Teachers

Abstract: The purpose of this study was to identify and assess the concerns of preservice physical education teachers at the University of Leuven (Belgium). In two studies, data were obtained with two different methodologies, namely a questionnaire and the logbook. In the first study the Teacher Concerns Questionnaire (TCQ) was administered to 100 students on three occasions during their early field teaching experiences. Of the three types of concern—self, task, and impact—only impact concern increased significantly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
16

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 10 publications
1
18
0
16
Order By: Relevance
“…Other studies have indicated low internal consistency and instability for the self concerns scale (e.g. Behets, 1990;Boggess, McBride and Griffey, 1985). Thus, the TCQ is not fully supported as an instrument for measuring students' concerns.…”
Section: Factor Analysismentioning
confidence: 96%
“…Other studies have indicated low internal consistency and instability for the self concerns scale (e.g. Behets, 1990;Boggess, McBride and Griffey, 1985). Thus, the TCQ is not fully supported as an instrument for measuring students' concerns.…”
Section: Factor Analysismentioning
confidence: 96%
“…Much research has been conducted on the concerns of trainee physical education teachers (e.g., Behets, 1990;Capel, 1997Capel, , 1998aCapel, , 1998bFuller 1969;Hardy, 1995Hardy, , 1996Mawer, 1995;McBride, Boggess and Griffey, 1986).…”
Section: Developing Knowledgeable Teachers Of Physical Education Ablementioning
confidence: 99%
“…Hayes et al (2008) note that in the extensive literature regarding the training of physical education (PE) teachers, much research has focused on beginner and expert teachers who face different concerns (Wendt et al, 1989;Behets, 1990Behets, , 1997Meek, 1996;Meek et al, 1999;Rossi et al, 2008). For example, Behets (1990) found several significant differences with respect to the instructional variables, all indicating that the most effective teachers spent significantly less time and attention on providing information to pupils. According to Castañer (1996) and Rossi et al (2008), the ‗putting into practice' employed by PE teachers bears a certain resemblance to the presentation of self that was described by Goffman (1959) in relation to our behaviour in space and time, and which in our view is associated with the kinesic and proxemic behaviours that form the object of the present study.…”
Section: Communication In Expert and Novice Teachersmentioning
confidence: 99%
“…Thus, regardless of a teacher's experience it is always worth questioning the forms and style of verbal and non-verbal communication used in everyday teaching practice, as well as the quality of the messages transmitted (Cloes et al, 1995). Hayes et al (2008) note that in the extensive literature regarding the training of physical education (PE) teachers, much research has focused on beginner and expert teachers who face different concerns (Wendt et al, 1989;Behets, 1990Behets, , 1997Meek, 1996;Meek et al, 1999;Rossi et al, 2008). For example, Behets (1990) found several significant differences with respect to the instructional variables, all indicating that the most effective teachers spent significantly less time and attention on providing information to pupils.…”
Section: Communication In Expert and Novice Teachersmentioning
confidence: 99%